Profile of Students' Mathematical Literacy in Solving Mathematics Problems Viewed from Learning Styles - Maria Irma Berek; Sumartono Sumartono; Lusiana Prastiwi (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Mathematical literacy is mathematics that has a different context to enable one to formulate, use and interpret mathematical problems and is very important in solving mathematical problems. This study aims to describe the profile of students' mathematical literacy in solving mathematical problems in relation to students' learning styles. This study uses a qualitative descriptive method with the subject matter of SMA Negeri 2 Trenggalek. Data collection techniques through questionnaires, interviews and documentation. The collected data was then analyzed in four steps, namely data reduction, triangulation, data presentation, and drawing conclusions. The results of the study show that the profile of mathematical literacy is more complete for visual learning styles than for auditory and kinesthetic learning styles.